2019
DOI: 10.1177/1179573519841623
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Therapy in a Community Setting for Independence, Mobility, and Sitting Balance for People With Spinal Cord Injuries

Abstract: Introduction: Activity-based therapy (ABT) aims to activate the neuromuscular system below the level of the spinal cord lesion and promote recovery of motor tasks through spinal reorganisation, motor learning and changes to muscles and sensory system. We investigated the effects of a multimodal ABT program on mobility, independence and sitting balance in individuals with spinal cord injury (SCI). Methods: Retrospective clinical data from 91 adults who independently enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
(84 reference statements)
2
6
0
Order By: Relevance
“…Our participants with chronic incomplete SCI improved reaching distance by ~ 13%, which is comparable to what has been reported after 30 sessions of supervised, laboratory-based kayak ergometers training in people with SCI 37 . Additionally, our results are consistent with the effect of activity-based therapy in the community in a similar population 39 , 40 . Conversely, two previous studies reported no improvement in reaching distance after a similar exercise program involving the upper body in people with chronic SCI; one study delivered 15 sessions of group-based arm-crank exercise 17 , while the other study conducted 8 sessions of indoor wheelchair curling training 41 .…”
Section: Discussionsupporting
confidence: 90%
“…Our participants with chronic incomplete SCI improved reaching distance by ~ 13%, which is comparable to what has been reported after 30 sessions of supervised, laboratory-based kayak ergometers training in people with SCI 37 . Additionally, our results are consistent with the effect of activity-based therapy in the community in a similar population 39 , 40 . Conversely, two previous studies reported no improvement in reaching distance after a similar exercise program involving the upper body in people with chronic SCI; one study delivered 15 sessions of group-based arm-crank exercise 17 , while the other study conducted 8 sessions of indoor wheelchair curling training 41 .…”
Section: Discussionsupporting
confidence: 90%
“… 6 12–16 Participation in ABT may prove beneficial across all degrees of severity and stages of injury (ie, acute, subacute and chronic stages), however, little is known about the characteristics and delivery of ABT across the continuum of care (ie, acute care, rehabilitation and community living). 16 Although ABT are gaining in popularity, there remain a number of challenges to their implementation in clinical practice. A lack of consensus regarding programme delivery and standardised guidelines, as well as available tools to effectively document participation and performance in ABT, limit the use of ABT in acute care, neurorehabilitation and community settings.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have showed that animals with a complete spinal cord transection (SCT) can step and stand with practice 16, 17. Activation of the neuromuscular system below the level of the spinal cord lesion by activity-based therapy (ABT) can lead to small improvements in mobility 18. Therefore, the performance of a motor task is improved by practicing a specific task with “challenges” added to a training regimen.…”
Section: Introductionmentioning
confidence: 99%